High temperature oxidation and corrosion of gas turbine materials in burner rig exposures. (1st July 2013) - Sumner, J; Encinas-Oropesa, A; Simms, N J; Oakey, J E
<x xml:space="preserve">Abstract</x> With the introduction of novel fuels, which may contain high levels of trace impurities including sulphur and alkali metals, industrial gas turbines are operating with increasingly corrosive combustion environments. To investigate the effect that this, coupled with the higher combustion gas temperatures needed to increase power plant efficiency, has on current state-of-the-art gas turbine component materials, three burner rig exposure tests have been run. The tests evaluated the effects of fly ash, gas moisture and gas temperatures on the alkali sulphate induced hot corrosion of CM247LC, Haynes 230, IN939 and IN728LC. Type I (sulphidation and internal damage), type II (pitting) and mixed mode hot corrosion were observed under different test conditions; however, the presence of fly ash appeared to reduce the levels of hot corrosion. CM247LC, with its high Al content improving oxidation resistance, showed less resistance to hot corrosion than the other, higher Cr content, alloys.